A new species of the genus Arcoptilia Arenberger (Lepidoptera, Pterophoridae) from Angola - Ustjuzhanin, P.; Kovtunovich, V. (Zootaxa, 2015)
The new species Arcoptilia naumanni sp. nov. (Lepidoptera, Pterophoridae) is described and illustrated from males found in Angola. Platyptilia rufamaculata Gielis, 2011, syn. nov. is established as a junior synonym of Arcoptilia pongola Ustjuzhanin & Kovtunovich, 2010.